Lymphatic vessels interact dynamically with the hair follicle stem cell niche during skin regeneration in vivo - Peña Jimenez, Daniel; Fontenete, Silvia; Megias, Diego; Fustero Torre, Coral; Graña Castro, Osvaldo; Castellana, Donatello; Loewe, Robert; Pérez Moreno, Mirna (My University, 2019)
Lymphatic vessels are essential for skin fluid homeostasis and immune cell trafficking. Whether the lymphatic vasculature is associated with hair follicle regeneration is, however, unknown. Here, using steady and live imaging approaches in mouse skin, we show that lymphatic vessels distribute to the anterior permanent region of individual hair follicles, starting from development through all cycle stages and interconnecting neighboring follicles at the bulge level, in a stem cell-depen dent manner. Lymphatic vessels further connect hair follicles in triads and dynamically flow across the skin. At the onset of the physiological stem cell activation, or upon pharmacological or genetic induction of hair follicle growth, lymphatic vessels transiently expand their caliber suggesting an increased tissue drainage capacity. Interestingly, the physiological caliber increase is associated with a distinct gene expression correlated with lymphatic vessel reorganization. Using mouse genetics, we show that lymphatic vessel depletion blocks hair follicle growth. Our findings point toward the lymphatic vasculature being important for hair follicle development, cycling, and organiza tion, and define lymphatic vessels as stem cell niche compo nents, coordinating connections at tissue-level, thus provide insight into their functional contribution to skin regeneration.